2017
DOI: 10.1002/syn.21991
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy improves cognitive deficit and neuronal morphology atrophy in the prefrontal cortex and hippocampus of aging spontaneously hypertensive rats

Abstract: It is well known that the survival is higher in women compared to men and women have a better survival prognosis than men in some pathologies such as vascular dementia (VD). Our previous reports showed that the spontaneously hypertensive (SH) rat, an animal model of VD, exhibited dendritic atrophy of pyramidal neurons of the dorsal hippocampus (DH) and the prefrontal cortex (PFC) at 8 months of age. Cerebrolysin (CBL), a neurotrophic peptide mixture, reduces dendritic atrophy and improves the memory process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 93 publications
(132 reference statements)
1
11
0
Order By: Relevance
“…N‐PEP‐12 also increases SYP and BDNF and reduces reactive gliosis in elderly animals. However, it is suggested that this dietary supplement formed by different neuropeptides with trophic action increases BDNF levels in different brain regions such as the hippocampus and PFC (Cabrera‐Pedraza et al, ; Hutter‐Paier et al, ; Solis‐Gaspar, Vazquez‐Roque, De Jesús Gómez‐Villalobos, & Flores, ), similar to what was observed in our results, where a greater immunoreactivity was shown for this neurotrophin in the five brain areas studied in elderly animals treated with N‐PEP‐12. In this sense, the expression of BDNF activates mechanisms of cell survival and protection, promotes the stimulation of synaptic connections, and increases the number of dendritic spines, as well as the dendritic tree, as our results show (Harward et al, ; Ohta et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…N‐PEP‐12 also increases SYP and BDNF and reduces reactive gliosis in elderly animals. However, it is suggested that this dietary supplement formed by different neuropeptides with trophic action increases BDNF levels in different brain regions such as the hippocampus and PFC (Cabrera‐Pedraza et al, ; Hutter‐Paier et al, ; Solis‐Gaspar, Vazquez‐Roque, De Jesús Gómez‐Villalobos, & Flores, ), similar to what was observed in our results, where a greater immunoreactivity was shown for this neurotrophin in the five brain areas studied in elderly animals treated with N‐PEP‐12. In this sense, the expression of BDNF activates mechanisms of cell survival and protection, promotes the stimulation of synaptic connections, and increases the number of dendritic spines, as well as the dendritic tree, as our results show (Harward et al, ; Ohta et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, by its characteristic conical shape, the ends of the dendrites must be positively identified to be included in the study. The pyramidal neurons were easily identified by the triangular form of their soma and by the extension of the apical dendrite toward the pial surface, apart from numerous dendritic spines (Cabrera‐Pedraza et al, ; Solís‐Gaspar et al, ; Tendilla‐Beltrán et al, ; Vidal et al, ). In the case of the PFC and CA1 region of DH and VH, the present analysis was performed on the basal dendrites, as they run parallel to the coronal plane.…”
Section: Methodsmentioning
confidence: 99%
“…Another assessment, the number of dendritic spines, was assessed by randomly selecting high‐magnification (1,000×) tracing of a 10‐µm‐long terminal segment of the distal branch exceeded 40 µm. Measurements of spine density were generated by counting the number of visible spines along the branch segment and expressing the data as number spines/10 µm (Cabrera‐Pedraza et al, ; Juarez et al, ; Juárez‐Méndez et al, ; Martinez‐Tellez., ; Monroy et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…With puberty the female brain is exposed to hormonal variations, primarily, the hormones related to the estrous cycle and second, at adult age, with the placental trophic factors and hormones related to gestation (for review see Dhoable, ; Sahay, Sundrani, & Joshi, ; Sahay, Sundrani, Wagh, Mehendale, & Joshi, ). Our recent report showed that one pregnancy improves the memory and learning process in aged spontaneously hypertensive (SH) female rats (12 months) (Cabrera‐Pedraza et al, ). In addition, the aged SH rats are considered an animal model of vascular dementia (Flores, Flores‐Gómez, & de Jesús Gómez‐Villalobos, ).…”
Section: Introductionmentioning
confidence: 99%